The Value of Legal Terminology for the Romano-German Legal System Countries - Sinenko, Vladimir S.; Latypov, Denis N.; Thabisimov, Husen A.; Shadzhe, Marina G.; Yah'yaeva, Marhat U. (International Journal of Criminology and Sociology, 2022)
The problems of terminology are relevant for any aspect of human life. In the field of lawmaking, the significance of this problem corresponds to the significance of laws in society. Thus, the primary aim of the article is to investigate the place of legal terminology in the countries of the continental system of law. To accomplish end, this survey attempts to substantiate that legal terminology in this legal system is of significant importance for the formation and application of legislation. To do so, a comparison is made with the construction of the legal system in the countries of the Anglo-Saxon legal system. Based on the result, Russian law is classified as a continental legal family. At the same time, based on an analysis of the key areas of development of economic legislation, a tendency has been revealed for the penetration of Anglo-Saxon legal institutions into the Russian legal system. The conclusion is formulated on the need to ensure the unity of legal terminology in legal texts. This is of particular importance when borrowing foreign legal institutions.